EL INSTITUTO DE INVESTIGACIONES SOCIALES (NOTAS SOBRE SU TRAYECTORIA HISTÓRICA) - Rovira Mas, Jorge (1994)
This article presents a careful revision of abundant academic work through nineteen years, made by the Social Research Institute. The mentioned institute belongs to the Social Sciences Faculty of the University of Costa Rica.